Strength Prediction and Optimization of Portland Limestone Cement Blended with Metakaolin and Rice Husk Ash - Musa Muhammad Jibrin; Olumide Olu Olubajo; Umar Omeiza Aroke (International Journal of Minerals, 2025)
This study explores the effects of Rice Husk Ash (RHA) and Metakaolin (MK) on the compressive strength of Portland Limestone Cement (PLC) mortar, aiming to promote sustainable construction materials. RHA and MK, derived from agricultural and industrial byproducts, serve as supplementary cementitious materials (SCMs) that offer environmental benefits and improve cement properties. Using response surface methodology (RSM) and central composite design (CCD), the research optimized the ternary blend of PLC, RHA, and MK to develop a predictive model for compressive strength, considering factors like blending ratio, replacement level, and curing age. The blending ratio denotes the proportion of RHA and MK to PLC, the replacement level is the percentage of PLC substituted by these SCMs, and curing age is the time allowed for mortar strength development. Various mortar samples with different RHA, MK, and PLC combinations were prepared, cured, and tested for compressive strength. The results showed that higher blending ratios, increased replacement levels, and longer curing ages enhanced mortar compressive strength. The optimal conditions identified were a blending ratio of 0.53, a replacement level of 3.40 wt.%, and a curing age of 56.30 days, yielding a compressive strength of 40.30 N/mm². This demonstrates that incorporating RHA and MK in PLC blends significantly enhances mortar strength, supporting sustainable construction practices. The paper emphasizes how RHA and MK can be used as SCMs to improve mechanical qualities and promote environmental sustainability. Future studies should look into these optimized blends' long-term durability and usefulness in diverse construction settings.
Keywords: Metakaolin; Optimization; Portland limestone cement; Response Surface Methodology; compressive strength; rice husk ash